Individual Counseling Cognitive Behavioral Therapy (CBT) To Improve Self-Confidence In Grade XI Students At SMA Negeri 2 Bontang Academic Year 2024/2025 - Cyntia Devi , Rossa; Sari Pratiwi, Yasintha; Sona , Dwi; Hidayanti , Nuril (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
Abstract This study aims to determine the effectiveness of individual cognitive behavioral therapy (CBT) counseling to increase self-confidence in class XI students at SMA Negeri 2 Bontang in the 2024/2025 Academic Year. This type of research is quantitative with a single-subject experimental design method using the A-B design type. This study only has 1 research subject where the subject was taken using purposive sampling with the characteristics of having problems often absent from school and low self-confidence. This study used a self-confidence scale data collection technique. Data analysis in this study used descriptive statistical techniques. The results of the data analysis of the implementation of individual CBT counseling services obtained an average score of 42.7 after being given treatment which showed high self-confidence, seen from the low overlapping percentage the subject got a result of 0% and changes in the direction of the trend showed an increase and the tendency of subject stability showed stable to the variable, it can be concluded that the implementation of individual counseling services is effective in increasing the self-confidence of class XI students at SMA Negeri 2 Bontang in the 2024/2025 Academic Year.